An Electronic Revenue Mobilization and Utilization System: Improving and Safeguarding the Tax for Development in the Builsa South District, Ghana - Amiisa, Gilbert; Azaare, Jacob; Zhao, Wu; Engmann, Gideon Mensah; Bernard John Tiika (Journal of Technology Management and Business, 2025)
The study designs and implements an online electronic tax payment system, BSDARMS, for the Builsa South District of Ghana, enabling taxpayers to track revenue utilization. Using the iterative waterfall model, BSDARMS provides a user-friendly interface, secure taxpayer database, and facilitates online payments via SMS and USSD. The system addresses limited revenue collection personnel, motivating business registration and tax compliance to support budget targets and district development. Compared to KRA’s ICT deployment, BSDARMS enhances operational efficiency by reducing administrative costs and revenue leakage. It aligns with Tanzania’s LGRCIS system, ensuring reliable tax collection and notification mechanisms.